This IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT BY APPLYING THEMATIC DISCUSSION AT SMP N 2 KOTA LANGSA - baihaqi baihaqi (Journal of Education, Linguistics, Literature and Language Teaching, 2018)
This research attempted to improve students' achievement in descriptive writing by applying Thematic Discussion. This research conducted by using classroom action research. The subject of the research was class VIII SMP N 2 Kota Langsa which consisted of 45 students. The research was conducted in two cycles; each cycle consisted of four meeting. The instruments for collecting data were quantitative data (writing test) and qualitative data (observation researcheret, questionnaire researcheret, and diary notes). Based on writing scores, students' score kept improving in every test and based on observation researcheret, questionnaire researcheret and diary notes, it was found that teachinglearning process ran well. Students were active, enthusiastic, and interested in writing. The result showed that Thematic Discussion technique significantly improved students' achievement in descriptive text writing